O ACESSO À JUSTIÇA POR MEIO DO NÚCLEO DE PRÁTICA JURÍDICA DA UNIVERSIDADE ESTADUAL DE PONTA GROSSA E A SOLUÇÃO DOS CONFLITOS FAMILIARES - Oliveira, Gisele Cristina de (2011)
The aim of this research is to analyse the possibility of access to justice by the economically vulnerable through the Public Defender‟s Office of State University Ponta Grossa and the its familiar conflicts solutions. The interest in this subject occured through the practice experience of the author as a collaborator professor of Civil Forensic Practice, acting in NPJ/UEPG between 2007 and 2010. The research has a quantitative characteristic, and it is performed through the following methodological procedure: referential systematization of methodological theoretical from the main analytics categories: economic vulnerability, access to justice, full legal assistance, Juridical Practice Center and familiar conflicts. Through this referential we can visualize the debate about the justice access in Brazil, in special for the economically vulnerable, identifying the access possibility for this group in relation to the Justice System, mainly by Juridical Practice Center of Law Courses. In this systematization was of fundamental importance the analyses about the access to Justice theory from Mauro Capelletti and Bryan Garth lessons and also the study about the new configurations of Brazilian contemporary family. In the sequence, it was made the documental research analyses based on Juridical Activities Report of NP/UEPG and in petitions under judgement by NPJ/UEPG between 2007 and 2010. The synthesis of this process resulted in positive results identification in relation to justice access through NPJ/UEPG for economically vulnerable who search this organ for familiar conflicts resolution.